The forgotten diaspora : Mesoamerican migrations and the making of the U.S.-Mexico borderlands - Jeffres, Travis (Borderlands and transcultural studies., 2023)
""The Forgotten Diaspora" explores how Native Mexicans involved in the conquest of the Greater Southwest pursued hidden agendas, exhibiting a covert agency that enabled them to reconstruct Indigenous communities and retain key components of their identities though technically allied with and subordinate to Spaniards"--